What drives performance in the speculative market of short-term exchange-traded retail products? - Stefanie Baller; Oliver Entrop; Alexander Schober; Marco Wilkens (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2017)
This paper considers the realized returns of individual investors in warrants and leverage certificates. First, we derive a general formula that analytically decomposes the return into several economically meaningful components that are related to investor's trading behavior and the issuers' price-setting strategy. Second, we use a large trade dataset to analyze returns along these components and also link them to investors' risk taking strategy. Our main findings are threefold: (i) The overall performance is poor. (ii) Investors show neutral timing skills, while the main performance driver is the issuers' price-setting. (iii) Higher risk taking by investors diminishes the performance further. Our results imply that retail investors do not achieve a pecuniary benefit from the considered financial innovations.
Keywords: D40; G11; G21; G24; 650; Leverage Certificate; Warrant; Financial Innovation; Retail Investor; Performance